Asian Americans, Admissions, and College Choice: An Empirical Test of Claims of Harm Used in Federal Investigations. (November 2020) - Nguyen, Mike Hoa; Chang, Connie Y.; Kim, Victoria; Gutierrez, Rose Ann E.; Le, Annie; Dumas, Denis; Teranishi, Robert T.
The Coalition of Asian American Associations (CAAA) and Asian American Coalition for Education (AACE), two small but vocal groups of Asian Americans, have argued against affirmative action practices. One of their more prominent claims is that Asian American applicants who are not accepted and do not attend their first-choice colleges face a multitude of negative consequences, a claim that has become the impetus for the current U.S. Department of Justice's investigation into the college admissions process at a number of universities. This study empirically tests the claims made by CAAA and AACE with particular attention to the differences in Asian American student outcomes, relative to their college admissions and choice decisions. Our findings indicate a limited, if any, statistical difference between Asian American groups that attend differing choice institutions.